Voltage control of the quantum scattering time in InAs/GaSb/InAs trilayer quantum wells. (3rd March 2023) - Meyer, M; Schmid, S; Jabeen, F; Bastard, G; Hartmann, F; Höfling, S
Abstract: We study the evolution of the quantum scattering time by gate voltage training in the topological insulator (TI) based on InAs/GaSb/InAs trilayer quantum wells. Depending on the minimal gate voltage applied during a gate voltage sweep cycle, the quantum scattering time can be improved by 50% from 0.08 ps to 0.12 ps albeit the transport scattering time is rather constant around 1.0 ps. The ratio of the quantum scattering time versus transport scattering time scales linearly with the charge carrier density and varies from 10 to 30, indicating Coulombic scattering as the dominant scattering mechanism. Our findings may enable to improve bulk and edge properties of TIs based on InAs/GaSb quantum well heterostructures solely by means of an electric field rather than temperature which opens the paths towards their application for macroscopic devices.